Rationale for the study of the human sex ratio in population studies of polluted environments - Jarrell John (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The human secondary sex ratio remains a subject of substantial interest. The possibility has been raised that environmental chemical exposures have played a role in the changes associated with the sex ratio in a number of countries. The possibility that such an effect may be present is supported at least theoretically by the observation that clomiphene citrate, a drug used in the treatment of infertility with powerful estrogenic and anti-estrogenic properties, has profound effects on the sex ratio resulting in significantly fewer males at birth. Using a model of causality based on the clinical identification of adverse drug effect methodology one may improve the objectivity of the assessment of significant environmental exposures on this human reproductive outcome.